Bilingualism in Language Variation in Modern Retail Businesses in Java Island Region: Bilingualisme dalam Variasi Bahasa pada Usaha Ritel Modern di Wilayah Pulau Jawa - Arif Fadillah Fadillah (Madah: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the forms of systemic language variation and language contact in retail monthly pamphlets and catalogs in Indonesia. To attract buyers, modern retailers usually make monthly pamphlets and catalogs that are distributed to a wide audience in public spaces. As language products, the pamphlets and catalogs of each modern retailer have their own linguistic phenomena. The data in this study were taken from thirteen modern retailers in Indonesia. The data were taken from the internet in the form of pamphlets or catalogs in May-June 2023. The data that has been obtained through observation is then classified and then analyzed and concluded. The results of this study found a form of systemic variation at the lexical, morphological, and syntactic levels. Syntactic variation dominates language variation in pamphlets. In addition, the form of language contact that appears in the data is bilingualism. The data shows bilingual contact in Indonesian and foreign languages. The dominating foreign language is English. The use of English is related to prestige and the purpose of attracting consumers.